Adaptive or maladaptive music-listening coping strategy: How does neuroticism use music after experiencing a romantic relationship breakup? - Hanwei He; Shu Chen; Cheng Hua (PLoS ONE, 2025)
Romantic relationship breakups are common experiences among young people and are associated with negative emotions that can jeopardize psychological well-being. Additionally, those with higher neuroticism may have greater emotional sensitivity towards the impact of music, as they tend to exhibit more negative and unstable emotional traits. As a result, they may be more inclined to control emotions by using music as a coping strategy. However, existing literature has rarely explored the differential roles of adaptive and maladaptive music-listening coping, as well as the mechanisms linking neuroticism and negative emotions associated with romantic breakups. To fill these gaps, the current study recruited 389 college students who had experienced at least one romantic breakup lasting two months or longer within the past five years. Participants completed a battery of questionnaires assessing relevant variables. Correlational analyses indicated that neuroticism and negative emotions related to romantic breakups were positively correlated with maladaptive music-listening coping. Conversely, neuroticism was negatively correlated with adaptive music-listening coping, while no discernible connection between adaptive music listening coping and negative emotions evoked by romantic breakups. Structural equation modeling suggested that neuroticism predicted emotional response to breakups through maladaptive music-listening coping, rather than adaptive music-listening coping. Theoretical and practical implications were discussed.